Effect of Kinesio taping on delayed-onset muscle soreness in elite athletes - Song, W.; Yang, Y. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: This research analyzes the effect of Kinesio taping on delayed-onset muscle soreness in elite athletes because delayed-onset muscle soreness increases the risk of injury in sports. METHODS: Elite female volleyball players (N.=31) were randomly divided into experimental (N.=16, with Kinesio taping of the knee) and control (N.=15) groups. To elicit delayed-onset soreness in knee joint muscles, the protocol that we used consisting of downhill running, visual analog pain score assessment, and measurements of serum interleukin-6 and creatine kinase concentrations immediately and after 24 hours, 48 hours, and 72 hours. RESULTS: Compared with the control group, the pain reported by the athletes with Kinesio taping decreased 24 hours and 48 hours (P<0.05) after running, but there was no significant difference 72 hours (P<0.05) after running. Interleukin-6 concentrations were lower in the athletes with Kinesio taping than those in the control group immediately and 24 hours (P<0.05) after running, but there was no significant difference 48 hours and 72 hours (P<0.05) after running. There were no significant differences (P>0.05) in creatine kinase concentrations. CONCLUSIONS: The use of Kinesio taping in elite athletes is an effective protective strategy for alleviating pain symptoms caused by delayed-onset muscle soreness, but it is not effective to alleviate the skeletal muscle microinjury caused by delayed-onset muscle soreness.